Labour Migration Governance in Times of Political Transition: A Comparative Analyisis of Egypt and Tunisia. (2nd January 2017) - Awad, Ibrahim; Selim, Hedayat
Abstract : The 2011 uprisings that culminated into the Arab Awakening were expected to engender seminal changes in the political systems of Egypt and Tunisia. Renewed calls to protect Egyptian and Tunisian migrants abroad were at first launched in the two countries. This paper examines patterns of continuity and change affecting policies and institutions of labour migration in Egypt and Tunisia. After outlining key institutions with mandate over labour migration, including a brief analysis of the two countries' labour markets, the paper assesses policies that promote employment abroad and protections for migrants. Egypt has made few changes in labour migration policies or institutions. Tunisia went further but without undertaking radical changes in its policies and institutions.